Identification, characterization, and expression analysis of WRKY transcription factors in Gynostemma pentaphyllum during tissue growth and cadmium stress - Zhou, Yunyi; Yao, Lixiang; Lu, Hai; Xiong, Zheng; Li, Xinhao; Yu, Liying; Pan, Chunliu (Frontiers in Plant Science, 2025)
Gynostemma pentaphyllum, a perennial medicinal herb, is widely distributed and exhibits remarkable adaptability to various environments. WRKY transcription factors play critical roles in regulating plant growth and development, as well as abiotic stress responses. However, the WRKY genes in G. pentaphyllum and their expression patterns under different tissues and Cd stress have not been thoroughly investigated, hindering our understanding of their role. In this study, 64 WRKY transcription factors identified in the G. pentaphyllum genome (GpWRKY) were phylogenetically grouped into three major groups and five subgroups and assigned a systematic nomenclature reflecting their positions across the 11 chromosomes. Comprehensive analyses of conserved domains, gene structures and motif features revealed a high degree of conservation with the gene family. Furthermore, seven pairs of segmental and tandem duplication events were detected, suggesting a contribution to the expansion of family. Cis-acting element analysis revealed the presence of hormone-related, stress-related, light-related, and development-related elements in the promoters of the majority of GpWRKY genes. Expression profiling analysis demonstrates that 64 GpWRKY genes were distinct in tissue-specific expression patterns and were substantially induced under Cd stress. Heterologous expression assay confirmed that GpWRKY48, one of the genes highly induced by Cd, positively regulates Cd tolerance. In this study, GpWRKY genes in G. pentaphyllum for the first time systematically identified and further investigated their physicochemical properties, evolution, and expression patterns, providing a theoretical basis for future studies on the functional characterization of G. pentaphyllum WRKY genes during plant growth and development, as well as Cd stress responses.